2013
DOI: 10.1155/2013/916348
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Primary T-Cell Central Nervous System Lymphoma: MR Imaging and MR Spectroscopy Assessment

Abstract: Primary central nervous system lymphomas (PCNSLs) are mainly B-cells lymphomas. A risk factor for the development of PCNSL is immunodeficiency, which includes congenital disorders, iatrogenic immunosuppression, and HIV. The clinical course is rapidly fatal; these patients usually present signs of increased intracranial pressure, nausea, papilledema, vomiting, and neurological and neuropsychiatric symptoms. PCNSL may have a characteristic appearance on CT and MR imaging. DWI sequences and MR spectroscopy may he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…The differential diagnosis include also primary CNS lymphomas (PCNSL), associated in almost 100% of the cases with EBV (2). Histological findings are almost always consistent with diffuse large cell non-Hodgkin's lymphomas (7). Different neurological deficits occur depending on the localization.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The differential diagnosis include also primary CNS lymphomas (PCNSL), associated in almost 100% of the cases with EBV (2). Histological findings are almost always consistent with diffuse large cell non-Hodgkin's lymphomas (7). Different neurological deficits occur depending on the localization.…”
Section: Introductionmentioning
confidence: 54%
“…More than four lesions of a primary CNS lymphomas are rarely found. The best method in establishing the diagnosis is MRS, which presents a variety of biochemical changes: lactate/lipid peak, increased choline/creatine and reduced N-acetylaspartate/creatine ratios in the lesion (5,7). Quantitative EBV PCR in the CSF improves the diagnostic specificity, although the predictive value remains too low for it to be used as an isolated marker for PCNSL (2).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present the case of a 10-year-old immunocompetent male with evolution of ALK-1-positive anaplastic T-cell lymphoma on MRI, visualized over 24 days with four MRIs. Despite numerous descriptions of radiographic features of PCNSL in immunocompetent patients, there has been no documentation of a PCNSL evolving so rapidly on serial imaging [6,7,9,11,12,13,25,26,27,28,29,30,31,32,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PCNSLs represented only 3–7% of primary brain tumors and 1–5% of all lymphomas. [ 1 2 ] Most of PCNSLs are B-cell lymphomas, while T-cell PCNSL (T-PCNSL) is extremely rare, the majority of the reported T-PCNSL cases are clinically sporadic that focus on the treatment, and its imaging features have rarely been described. [ 1 3 4 ] Herein, we report a case of T-PCNSL and comprehensively summarize its magnetic resonance imaging (MRI) characteristics.…”
mentioning
confidence: 99%
“…T-PCNSL is rare and highly malignant tumor type of CNS, associated with poor prognosis. [ 1 ] Immunodeficiency is a risk factor for T-PCNSL, and the predilection age ranges from 55 to 57 years. [ 3 ] Other than surgical resection for other CNS malignant tumors such as glioma and solitary metastasis, a combination of chemotherapy and radiotherapy is the most preferred treatment for T-PCNSL.…”
mentioning
confidence: 99%